A2_3 Deep Space 2: Journey to another star - Forster, James; Bryan, Mark; Stone, Alex (Physics Special Topics, 2012)
In designing a "Generation Ship", this paper discusses the relativistic eects on the velocity and travel time of a journey at an initial 1g acceleration to the star system Alpha Centauri. It was found that such a journey would take 3.8 years for the crew, 6.5 years for an observer on Earth and would have a peak velocity of 0.89c.